2003
DOI: 10.1128/iai.71.1.428-436.2003
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Patterns of Colonization and Immune Response Elicited from Two IntestinalLactobacillusStrains That Display Similar Properties In Vitro

Abstract: Lactobacilli derived from the endogenous flora of normal donors are being increasingly used as probiotics in functional foods and as vaccine carriers. However, a variety of studies done with distinct strains of lactobacilli has suggested heterogeneous and strain-specific effects. To dissect this heterogeneity at the immunological level, we selected two strains of lactobacilli that displayed similar properties in vitro and studied their impact on mucosal and systemic B-cell responses in monoxenic mice. Germfree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
127
2
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(140 citation statements)
references
References 44 publications
3
127
2
8
Order By: Relevance
“…Change in cholesterol level was not unexpected as over several years, more and more experimental and clinical trials indicated that probiotics could lead to a decrease in serum cholesterol (22)(23)(24)(25)(26). Findings of a recent metaanalysis indicated that probiotics had a significantly good effect on normalizing total cholesterol, as we observed (27).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Change in cholesterol level was not unexpected as over several years, more and more experimental and clinical trials indicated that probiotics could lead to a decrease in serum cholesterol (22)(23)(24)(25)(26). Findings of a recent metaanalysis indicated that probiotics had a significantly good effect on normalizing total cholesterol, as we observed (27).…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, fermentation products of lactic acid bacteria inhibit cholesterolsynthesizing enzymes and thus reduce cholesterol production. The bacteria may facilitate elimination of cholesterol in feces and may inhibit its reabsorption into the body; in addition, these bacteria may interfere with the recycling of bile salt (a metabolic product of cholesterol) (22,24). We observed no effect on HDL level, may be HDL requires longterm intervention to change or there are unknown mechanisms in this regard (27).…”
Section: Discussioncontrasting
confidence: 49%
“…9 Whereas priming of T cells in Peyer's patches or MLNs leads to effective local (mucosal) immune responses or tolerance depending on the encountered antigen, systemic immune responses or tolerance to ingested antigens are likely to be generated in the MLNs. 6 The translocation effi ciency of commensal (and presumably probiotic) bacteria depends on the bacterial strain and the luminal concentration, 10,11 but the percentage of orally administered commensal bacteria that can be recovered from DCs in MLNs is very small. 12 Effi cient killing by macrophages and sequestering in MLN DCs largely prevent commensal bacteria from gaining access to the systemic immune compartment.…”
Section: Introductionmentioning
confidence: 99%
“…johnsonii NCC 533 (formerly Lactobacillus acidophilus La1), a human isolate (10), has been extensively studied for its probiotic-associated activities, including immunomodulation (11)(12)(13), pathogen inhibition (14), and epithelial cell attachment (15,16). To rapidly advance our understanding of Lactobacillus physiology and to identify potential bacterial components involved in host interactions, we sequenced and analyzed the genome of L. johnsonii NCC 533.…”
mentioning
confidence: 99%